Perbedaan Pemilihan Waktu Cold Water Immersion Terhadap Timbulnya Delayed Onset Muscle Soreness Setelah Latihan Submaksimal - Wilson Arpin; Dhoni Akbar Gozali; Yunia Hastami; Selfi Handayani (Journal of Sport Science and Education, 2020)
This study aims to knowing the differences in effectiveness of the timing cold water immersion against the onset of delayed onset muscle soreness after submaximal exercise. This research is an experimental study with posttest-only with control group design. The pain of delayed onset muscle soreness measured by Visual Analog Scale. The subjects were 30 samples, which split into 3 groups. Data analysis to determine the result of this study used the one way ANOVA with Î± determined at 0.05. The result of this study indicate that there are significant differences in each group, the group that received the immersion had a lower pain scale than the control group, also the group that was treated 1 hour after exercise showed better results than the 4 hours, CWI after 1 hour after exercise can inhibit migration of neutrophils which are the main cells of secondary damage that will induce pain. The conclusion of this study is cold water immersion after 1 hour after exercise is better than the 4 hours.